Method for preparing diamond through low-pressure phase change of graphite
By combining tantalum wire deposition and hydrogen plasma treatment in HFCVD and MPCVD systems, the limitations of high-temperature and high-pressure method and detonation method in the preparation of diamond are solved, and efficient preparation of graphite conversion to diamond under low pressure is achieved. Larger size and more diamond particles and improves the economical and environmental protection of the process.
Patent Information
- Application Number
- CN202411350219.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
AI Technical Summary
The existing high-temperature and high-pressure methods and detonation methods have limitations in the preparation of diamonds, such as high cost, complex purification processes and small diamond particle size problems, and the formation of tantalum oxide during hot wire deposition reduces monodispersed Ta. The amount of atoms.
After the single crystal scale graphite sheet is pressed by a fully automatic tablet press, and Ta atoms are deposited in the HFCVD system, the hydrogen plasma treatment is used in the MPCVD system to reduce tantalum oxide, which promotes the conversion of graphite into diamond under low pressure.
It has achieved the acquisition of more quantity and larger size diamond particles under low pressure, and the process is simple, the cost is low, energy-saving and environmentally friendly, the equipment requirements are low, and the operation is relatively simple.
Smart Images

Figure HDA0005062149060000011 
Figure HDA0005062149060000012 
Figure HDA0005062149060000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing diamond, and in particular to a new method for preparing diamond by promoting graphite phase change under low pressure. Background Art
[0002] Diamond has excellent mechanical, electrical, thermal, acoustic and optical properties due to its unique crystal structure, and has broad application prospects in industrial production, electronic appliances and other fields. However, the reserves of natural diamonds in nature are relatively scarce, resulting in high prices. Synthetic diamonds are highly similar to natural diamonds in crystal structure and physical and chemical properties, and are widely used in the field of industrial production. Moreover, their cost is relatively low, and they have significant economic advantages. Therefore, the technology of artificial diamonds has developed rapidly, which not only meets the urgent needs of economic construction, but also promotes the development of scientific and technological progress. As two common allotropes of carbon, the study of the mutual transformation of graphite and diamond has long attracted attention. At present, the high temperature and high pressure method and the detonation method are the two most common methods for preparing diamonds using graphite as raw materials. As a typical synthesis method, high temperature and high pressure has become one of the most common methods for synthesizing diamonds in industry after years of research. The high temperature and high pressure method completely simulates the natural mechanism of natural diamond growth underground. Generally, pressure and temperature above 10GPa and 3000℃ are required to allow the carbon atoms in graphite to recombine into the structure of diamond. The detonation method uses the instantaneous high temperature and high pressure environment generated by the explosion of high explosives to produce nano diamond particles. The nano diamonds obtained by this method have a large output, but the diamond particles are small in size and mixed with the raw materials, which makes post-processing very difficult and the purification process very complicated. Both methods have certain limitations. Therefore, it is urgent to develop a new method for preparing diamonds.
[0003] The inventor's previous research shows that the diamond grown by the hot wire chemical vapor deposition (HFCVD) equipment using tantalum wire as a heat source is derived from the phase transition of graphite under the action of Ta atoms; and it is proved that Ta atoms can spontaneously transform graphite into diamond, which provides a new idea for the preparation of diamond based on graphite. The inventor also used tantalum wire in the HFCVD system as a tantalum source in the early stage to deposit Ta atoms on the surface of the pressed graphite sheet, and obtained diamond after annealing (see patent document CN202310059001.2). The substrate used in the patent document is pressed from graphite powder of smaller size (particle size 1μm), which limits the size of the diamond obtained by phase change. Based on this factor, the inventor used larger single crystal flake graphite (particle size 5μm) as a substitute, and obtained larger diamonds by changing the tantalum wire processing gas pressure and annealing temperature in the HFCVD system (see patent document CN202311754625.2). However, the above methods will inevitably form tantalum oxide during the hot wire deposition of Ta, reducing the amount of monodisperse Ta atoms. Therefore, in the present application, the inventors used single crystal flake graphite with deposited Ta as a substrate, and reduced tantalum oxide with hydrogen plasma in a microwave plasma chemical vapor deposition (MPCVD) system to convert more tantalum oxide into monodisperse Ta atoms, thereby promoting the transformation of graphite into diamond under low pressure. Summary of the invention
[0004] The present invention provides a method for preparing diamond by low-pressure phase change of graphite. The method uses a fully automatic tablet press to press single-crystal flake graphite powder into graphite sheets, which are then placed in an HFCVD system, Ta atoms are deposited on the surface of the graphite sheets, and then the graphite sheets loaded with Ta atoms are placed in an MPCVD system for hydrogen plasma treatment, thereby converting graphite into diamond under low pressure.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing diamond by low-pressure phase change of graphite, comprising the following steps:
[0007] (1) Preparing single crystal flake graphite sheets: placing single crystal flake graphite powder into a tablet press and pressing it into single crystal flake graphite sheets;
[0008] Tablet press operating parameters: apply 30MPa pressure, maintain the pressure and press for 2min;
[0009] The preferred single crystal flake graphite sheet has a diameter of 13 mm and a thickness of 1.1 mm;
[0010] (2) Tantalum wire treatment: Raise the HFCVD bell jar, install the tantalum wire on the fixture, place the single crystal flake graphite sheet obtained in step (1) as a substrate on the sample stage in the HFCVD equipment, with the graphite sheet located directly below the tantalum wire, lower the bell jar, evacuate the chamber, introduce hydrogen into the chamber, and then perform tantalum deposition for 15 min at a power of 400 W;
[0011] The hydrogen flow rate is preferably 200 sccm, and the gas pressure is stabilized at 1.0 to 5.0 kPa (preferably 3 kPa);
[0012] The tantalum wire is in a double helix shape. This step of tantalum wire processing does not require a carbon source. Instead of chemical vapor deposition, the Ta wire in the equipment is used as a heat source and tantalum source for tantalum deposition.
[0013] (3) Hydrogen plasma treatment: placing the graphite sheet treated with tantalum wire in step (2) in an MPCVD system and treating it with hydrogen plasma for 10 to 60 minutes (preferably 20 minutes);
[0014] The preferred MPCVD system has a microwave hydrogen treatment power of 700W, a working gas pressure of 2.0 torr, and a hydrogen flow rate of 100 sccm;
[0015] (4) Annealing treatment: The graphite sheet treated with hydrogen plasma in step (3) is sealed in a vacuum quartz tube, and then the quartz tube is placed in a muffle furnace at 900° C. for annealing for 15 to 90 minutes (preferably 30 minutes) to obtain diamond on the graphite sheet.
[0016] Compared with the existing process of converting graphite into diamond under high temperature and high pressure, the beneficial effects of the present invention are as follows:
[0017] 1. The metal tantalum atoms released when the tantalum wire is heated in the HFCVD system are deposited on the graphite sheet, and then treated with hydrogen plasma to convert more tantalum oxide formed during the Ta deposition process into monodisperse Ta atoms, promoting the transformation of graphite into diamond under low pressure. It has the advantages of low cost, energy saving and environmental protection.
[0018] 2. This method has low equipment requirements, simple process and easy operation.
[0019] 3. Compared with the previous process of converting graphite into diamond under low pressure by the research team (see patent document CN202210305804.7), the present invention obtains more diamonds with larger sizes, providing a more feasible solution for preparing diamonds based on phase change of graphite under low pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 : Scanning electron microscope (SEM) image of intrinsic flake graphite.
[0021] Figure 2: Transmission electron microscope (TEM) image of intrinsic flake graphite.
[0022] Figure 3 : SEM image of Example 1 (HFCVD power 400 W-tantalum wire treatment 15 min-MPCVD power 700 W-hydrogen plasma treatment 10 min).
[0023] Figure 4 : TEM image of Example 1 (400W-15min-700W-10min).
[0024] Figure 5 : SEM image of Example 2 (400W-15min-700W-20min).
[0025] Figure 6 : TEM image of Example 2 (400W-15min-700W-20min).
[0026] Figure 7 : SEM image of Example 3 (400W-15min-700W-40min).
[0027] Figure 8 : TEM image of Example 3 (400W-15min-700W-40min).
[0028] Fig. 9 : SEM image of Example 4 (400W-15min-700W-60min).
[0029] Fig.10 : TEM image of Example 4 (400W-15min-700W-60min). DETAILED DESCRIPTION
[0030] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.
[0031] In the following embodiments,
[0032] Single crystal flake graphite powder is produced by Qingdao Mingheda Graphite New Materials Co., Ltd. with a purity of 99% and a particle size of 100 mesh.
[0033] The tablet pressing equipment was developed by Tianjin Botian Shengda Technology Development Co., Ltd. and its model is FW-4A.
[0034] The HFCVD equipment was developed by Shanghai Jiao Tong University and its model is JUHFCVD001.
[0035] The MPCVD equipment was developed by Taiwan Shuojie Enterprise Co., Ltd. and its model is MP-R100.
[0036] Example 1
[0037] (1) Single crystal flake graphite powder was placed in a tablet press, a pressure of 30 MPa was applied, and the pressure was maintained and pressed for 2 minutes to prepare single crystal flake graphite sheets with a diameter of 13 mm and a thickness of 1.1 mm.
[0038] (2) The HFCVD bell jar was raised, and the double-helix tantalum wire was mounted on the fixture. The single-crystal flake graphite sheet pressed in step (1) was placed as a substrate in the HFCVD equipment for tantalum deposition. Hydrogen gas with a flow rate of 200 sccm was introduced into the chamber, and the pressure in the chamber was stabilized at 3 kPa. Subsequently, the tantalum wire was treated for 15 min at a power of 400 W.
[0039] (3) The sample after tantalum wire treatment was treated with hydrogen plasma in an MPCVD system for 10 min. The microwave hydrogen treatment power was 700 W, the working gas pressure was 2.0 torr, and the hydrogen flow rate was 100 sccm.
[0040] (4) Annealing treatment: The graphite sheet treated in step (3) is placed in a quartz tube and sealed. The quartz tube is evacuated while sealing to ensure that the quartz tube is in a near-vacuum state. The sealed quartz tube (with the sample inside) is placed in a muffle furnace at 900° C. After annealing for 30 minutes, the sample is taken out to complete the annealing process.
[0041] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.
[0042] Figure 1 This is a SEM image of intrinsic flake graphite. Because it is pressed from single crystal flake graphite sheets, the surface is locally flat, and obvious wrinkles appear at the junction of the sheets.
[0043] Figure 2This is a TEM image of intrinsic flake graphite. From the low-magnification display (a), it can be seen that the edge of the sample is a large-area lamellar structure. Selected area electron diffraction (SAED) SAED-a mainly contains diffraction rings of graphite (201), (110), (101) and (100) crystal planes, indicating that the sample is mainly composed of graphite structure, and no diffraction information of other phases is found. (b) is a high-magnification display of area b in (a). In the Fourier transform (FT) FT-b of this area, there are three pairs of diffraction points with a crystal plane spacing of 0.213nm. b-1 is an enlargement of area 1 in b, showing that area 1 includes three pairs of crystal planes with a spacing of 0.213nm and an angle of 60°, which is consistent with the angle of the graphite (100) crystal plane. The above results show that intrinsic graphite exists in the form of large-area flat lamellar graphite (100) crystal planes.
[0044] Figure 3 This is the SEM picture of Example 1. Compared with the SEM of intrinsic flaky graphite flakes, snowflake-like particles are generated on the surface of the sample after microwave hydrogen treatment.
[0045] Figure 4 The TEM images of Example 1, (a) is a low-magnification display of a sample treated with microwave hydrogen for 10 minutes, and clusters connected into sheets were found at the edge of the thin area of the sample, and no dendritic particles were found. SAED-a shows the diffraction information of graphite (201), (110), (101), (100) crystal planes and two pairs of diamond (111) planes. (b)-(d) are high-magnification displays of areas bd, and both contain particles with clear boundaries from the graphite (100) plane. Further analysis of the particles, b-1 shows that the particles have two pairs of coherent crystal planes with a crystal plane spacing of 0.206nm, and FT-b1 also shows the corresponding two pairs of diffraction points. After measurement, the crystal plane angle is 70°, which is consistent with the spacing and angle of the diamond (111) plane. There are stripes with a spacing of 0.206nm inside the particles of c-1 and d-1, and there are corresponding diffraction points in FT-c1 and FT-d1, which are similar to the diffraction information of the cubic diamond (111) crystal plane. The above results show that in the sample treated with microwave hydrogen for 10 minutes, multiple diamond particles with a size of 15-30nm can be found in the graphite thin area without dendrite structure.
[0046] Example 2
[0047] (1) Single crystal flake graphite powder was placed in a tablet press, a pressure of 30 MPa was applied, and the pressure was maintained and pressed for 2 minutes to prepare single crystal flake graphite sheets with a diameter of 13 mm and a thickness of 1.1 mm.
[0048] (2) The HFCVD bell jar was raised, and the double-helix tantalum wire was mounted on the fixture. The single-crystal flake graphite sheet pressed in step (1) was placed as a substrate in the HFCVD equipment for tantalum deposition. Hydrogen gas with a flow rate of 200 sccm was introduced into the chamber, and the pressure in the chamber was stabilized at 3 kPa. Subsequently, the tantalum wire was treated for 15 min at a power of 400 W.
[0049] (3) The sample after tantalum wire treatment was treated with hydrogen plasma in an MPCVD system for 20 min. The microwave hydrogen treatment power was 700 W, the working gas pressure was 2.0 torr, and the hydrogen flow rate was 100 sccm.
[0050] (4) Annealing treatment: The graphite sheet treated in step (3) is placed in a quartz tube and sealed. The quartz tube is evacuated while sealing to ensure that the quartz tube is in a near-vacuum state. The sealed quartz tube (with the sample inside) is placed in a muffle furnace at 900° C. After annealing for 30 minutes, the sample is taken out to complete the annealing process.
[0051] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.
[0052] Figure 5 This is the SEM picture of Example 2. Compared with the SEM picture of Example 1, the snowflake-like particles generated on the surface after microwave hydrogen treatment are more dense and uniform, and the size of the snowflake-like particles and the distance between the particles are increased.
[0053] Figure 6The TEM images of Example 2 are shown in (a) at a low magnification of the sample treated with microwave hydrogen for 20 minutes. It can be seen that the sample contains a large number of dendrite-like particles with further increased size, which is consistent with the SEM results. In addition, a relatively special particle with a size of about 50nm was found, as shown by the red dotted line in (b). There are two pairs of coherent crystal planes with a spacing of 0.208nm inside the particle, and the angle is 70°. There is a diffraction point with a corresponding angle of 70° in FT-b1, which meets the standard crystal plane spacing and crystal plane angle of cubic diamond, and is the diamond (111) plane. (c) is another low magnification display of the sample treated with microwave hydrogen for 20 minutes. It can be found that there are many spherical particles in the thin area of the sample. SAED-c shows that the main diffraction information at this position is graphite (201), (110), (101), (100), (002) crystal planes and a pair of diamond (111) crystal planes. (d) is a high magnification display of area d, where there are particles with deep contrast. d-1 shows that there are lattice fringes with a spacing of 0.209nm inside the particle, and FT-d1 shows the corresponding diffraction points, which belong to the diamond (111) plane. From the high-power display (e), it is found that there is a spherical particle with a size of about 50nm in area e. FT-e shows that there are only diffraction points of 0.207nm in this area. Through Fourier inverse transformation (IFT-e), it is found that the 0.207nm fringes exist within the red dotted line inside the particle. e-1 and FT-e1 also prove that there are 0.207nm fringes in the dotted line, which is consistent with the spacing of the diamond (111) plane, indicating that there is a diamond particle inside the amorphous carbon sphere and it is in the process of transforming into diamond. The above analysis shows that the sample treated with microwave hydrogen for 20 minutes has larger diamond particles near the dendrite particles, and more diamond particles with a size of 10-50nm can be found in the graphite thin area without dendrite structure. Compared with the 5-15 nm diamonds obtained in previous patent documents, the size of the diamonds obtained in the present invention is significantly increased.
[0054] Example 3
[0055] (1) Single crystal flake graphite powder was placed in a tablet press, a pressure of 30 MPa was applied, and the pressure was maintained and pressed for 2 minutes to prepare single crystal flake graphite sheets with a diameter of 13 mm and a thickness of 1.1 mm.
[0056] (2) The HFCVD bell jar was raised, and the double-helix tantalum wire was mounted on the fixture. The single-crystal flake graphite sheet pressed in step (1) was placed as a substrate in the HFCVD equipment for tantalum deposition. Hydrogen gas with a flow rate of 200 sccm was introduced into the chamber, and the pressure in the chamber was stabilized at 3 kPa. Subsequently, the tantalum wire was treated for 15 min at a power of 400 W.
[0057] (3) The sample after tantalum wire treatment was treated with hydrogen plasma in an MPCVD system for 40 min. The microwave hydrogen treatment power was 700 W, the working gas pressure was 2.0 torr, and the hydrogen flow rate was 100 sccm.
[0058] (4) Annealing treatment: The graphite sheet treated in step (3) is placed in a quartz tube and sealed. The quartz tube is evacuated while sealing to ensure that the quartz tube is in a near-vacuum state. The sealed quartz tube (with the sample inside) is placed in a muffle furnace at 900° C. After annealing for 30 minutes, the sample is taken out to complete the annealing process.
[0059] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.
[0060] Figure 7 This is the SEM picture of Example 3. Compared with the SEM pictures of Examples 1 and 2, the snowflake-like particles generated on the surface after microwave hydrogen treatment are larger in size and more densely packed.
[0061] Figure 8 The TEM images of Example 3, (a) is a low-magnification display of the sample treated with microwave hydrogen for 40 minutes, and it can be found that the sample also has a large number of dendrite particles. (b) is a high-magnification display of area b. FT-b has a pair of 0.206nm diffraction points, and FT-b1 and (b-1) show that the 0.206nm stripe exists in the red dotted area, which is close to the diffraction information of the diamond (111) crystal plane, so it is considered to be diamond. Therefore, after microwave hydrogen treatment and annealing for 40 minutes, diamonds with a size of about 20-30nm also exist in the sample.
[0062] Example 4
[0063] (1) Single crystal flake graphite powder was placed in a tablet press, a pressure of 30 MPa was applied, and the pressure was maintained and pressed for 2 minutes to prepare single crystal flake graphite sheets with a diameter of 13 mm and a thickness of 1.1 mm.
[0064] (2) The HFCVD bell jar was raised, and the double-helix tantalum wire was mounted on the fixture. The single-crystal flake graphite sheet pressed in step (1) was placed as a substrate in the HFCVD equipment for tantalum deposition. Hydrogen gas with a flow rate of 200 sccm was introduced into the chamber, and the pressure in the chamber was stabilized at 3 kPa. Subsequently, the tantalum wire was treated for 15 min at a power of 400 W.
[0065] (3) The sample after tantalum wire treatment was treated with hydrogen plasma in an MPCVD system for 60 min. The microwave hydrogen treatment power was 700 W, the working gas pressure was 2.0 torr, and the hydrogen flow rate was 100 sccm.
[0066] (4) Annealing treatment: The graphite sheet treated in step (3) is placed in a quartz tube and sealed. The quartz tube is evacuated while sealing to ensure that the quartz tube is in a near-vacuum state. The sealed quartz tube (with the sample inside) is placed in a muffle furnace at 900° C. After annealing for 30 minutes, the sample is taken out to complete the annealing process.
[0067] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.
[0068] Fig. 9 This is the SEM picture of Example 4. Compared with the SEM images of intrinsic flake graphite, Example 1, Example 2, and Example 3, the size of the snowflake-shaped particles is further increased, and as the treatment time increases, the boundaries between the particles become more obvious, and the size of the particles gradually increases, reaching the maximum size at 60 minutes.
[0069] Fig.10 The TEM images of Example 4 are shown in Figure (a). The low-magnification display of the sample treated with microwave hydrogen for 60 minutes shows that a small amount of particles exist in the thin area of the sample. The diffraction information of graphite (201), (110), (101), (100) crystal planes and a pair of diamond (111) crystal planes are mainly present in SAED-a. (b)-(d) are high-magnification displays of regions bd. There are lattice fringes inside the amorphous carbon spheres in the three regions. Further analysis of the internal fringes of the amorphous carbon spheres shows that there are lattice fringes of about 0.206nm in b-1, c-1 and d-1. FT-b1, FT-c1 and FT-d1 all show corresponding diffraction points, which are consistent with the spacing of the diamond (111) plane. After analysis, it is believed that the areas surrounded by red dotted lines in these amorphous carbon spheres are all diamonds. The above results show that after microwave hydrogen treatment for 60 minutes annealing, a large number of diamond particles with a size of 20-30nm can be found in the graphite thin area without dendritic structure.
Claims
1. A method for preparing diamond by low-pressure phase change of graphite, characterized in that: The following steps are involved: (1) Preparing single crystal flake graphite sheets: placing single crystal flake graphite powder into a tablet press and pressing it into single crystal flake graphite sheets; (2) Tantalum wire treatment: Raise the HFCVD bell jar, install the tantalum wire on the fixture, place the single crystal flake graphite sheet obtained in step (1) as a substrate on the sample stage in the HFCVD equipment, with the graphite sheet located directly below the tantalum wire, lower the bell jar, evacuate the chamber, introduce hydrogen into the chamber, and then perform tantalum deposition for 15 min at a power of 400 W; (3) Hydrogen plasma treatment: placing the graphite sheet treated with tantalum wire in step (2) in an MPCVD system and treating it with hydrogen plasma for 10 to 60 minutes; (4) Annealing treatment: The graphite sheet treated with hydrogen plasma in step (3) is sealed in a vacuum quartz tube, and then the quartz tube is placed in a muffle furnace at 900° C. for annealing for 15 to 90 minutes to obtain diamond on the graphite sheet.
2. The method for preparing diamond by low-pressure phase change of graphite as claimed in claim 1, characterized in that: In step (1), the tablet press operating parameters are: applying a pressure of 30 MPa, maintaining the pressure and pressing for 2 minutes.
3. The method for preparing diamond by low-pressure phase change of graphite as claimed in claim 1, characterized in that: In step (1), the diameter of the single crystal flake graphite sheet is 13 mm and the thickness is 1.1 mm.
4. The method for preparing diamond by low-pressure phase change of graphite as claimed in claim 1, characterized in that: In step (2), the flow rate of hydrogen is 200 sccm, and the gas pressure is stabilized at 1.0-5.0 kPa.
5. The method for preparing diamond by low-pressure phase change of graphite as claimed in claim 1, characterized in that: In step (3), the microwave hydrogen treatment power of the MPCVD system is 700 W, the working gas pressure is 2.0 torr, and the hydrogen flow rate is 100 sccm.
6. The method for preparing diamond by low-pressure phase change of graphite as claimed in claim 1, characterized in that: In step (3), hydrogen plasma treatment is performed for 20 minutes.
7. The method for preparing diamond by low-pressure phase change of graphite as claimed in claim 1, characterized in that: In step (4), annealing is performed for 30 minutes.
